USE OF INNOVATIVE EDUCATIONAL TECHNOLOGIES IN THE SCIENCE OF MOLECULAR GENETICS - Daminov M. A. (Web of Journals Publishing, 2024)
This article provides information on the effectiveness of increasing the learning ability and cognitive potential of students through the use of innovative educational technologies in teaching molecular genetics.
Keywords: innovative educational technologies, molecular genetics, creative technologies, didactic games.